Zero Echo Time and Similar Techniques for Structural Changes in the Sacroiliac Joints - Serfaty, Aline; Pereira, Diogo Miguel Machado; Cantarelli Rodrigues, Tatiane (Seminars in Musculoskeletal Radiology, 2025)
Spondyloarthritis (SpA) encompasses inflammatory disorders affecting the axial skeleton, with sacroiliitis as a hallmark feature of axial SpA (axSpA). Imaging plays a vital role in early diagnosis and disease monitoring. Magnetic resonance imaging (MRI) is the preferred modality for detecting early inflammatory changes in axSpA, whereas structural lesions are better visualized using computed tomography (CT). However, synthetic computed tomography (sCT), a technique that generates CT-like images from MRI data, including deep learning methods, zero echo time, ultrashort echo time, and gradient-recalled echo sequences, has emerged as an innovative tool. It offers detailed anatomical resolution without ionizing radiation and combines the advantages of both, MRI and CT, by enabling the simultaneous evaluation of inflammatory and structural lesions. This review explores the potential role of MRI-based sCT in assessing structural changes in the sacroiliac joints, particularly in the context of axSpA, discussing conventional imaging and highlighting the potential of sCT to enhance early detection and monitoring of sacroiliitis.
Keywords: synthetic computed tomography; spondyloarthritis; sacroiliac joints; magnetic resonance imaging; axial spondyloarthritis